DESAIN MINIATUR MEANDER PLANAR INVERTED F ANTENNA PADA 915 MHZ UNTUK TANGAN BIONIK MENGGUNAKAN DESIGN OF EXPERIMENT - Liya Yusrina Sabila; Teguh Prakoso; Munawar Agus Riyadi (TESLA: Jurnal Teknik Elektro, 2022)
To improve the quality of the bionic hands used by some disabled people, new innovations are needed. By implementing IoT in the development of bionic hands, it can make it easier for patients to obtain information, such as monitoring battery capacity, bionic hand life, and bionic hand health. So we need a component that is able to transmit this information. In this paper, we are the Meander Planar Inverted F Antenna (PIFA) at a frequency of 915 – 925 MHz which is compatible with Sigfox or LoRa IoT technology. The antenna is designed to have miniature characteristics so that it does not interfere with other components when implanted in the bionic arm and is curved so that it can follow the curved shape of the bionic arm. The miniature technique used is the winding technique and the conformal technique is used to give a curved effect to the antenna. The design is carried out very systematically by streamlining the steps using the Design of Experiment method. It is proven that it only takes 6 steps to get results that match the specifications. The simulation results show the value of S11 is -21 dB, resonant frequency is 924.9 MHz, bandwidth is 13.5 MHz, gain is -23.34 dBi and radiation pattern is omnidirectional.